2011
DOI: 10.1111/j.1600-0536.2011.01992.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of p‐phenylenediamine and 2‐hydroxy‐1,4‐naphthoquinone in henna tattoos

Abstract: Products purporting to be henna, but that in fact contain no henna, are being offered. Moreover, these products may contain PPD, which is associated with health risks, especially severe allergic reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 17 publications
(18 reference statements)
2
42
1
1
Order By: Relevance
“…The potency of PPD as an allergen is directly related to its concentration and the duration of exposure to the skin; as vendors of black henna are entirely unregulated, the concentration of PPD can reach up to 16%, far in excess of that permissible in hair dyes [2,7,8]. Discordance between siblings who are both exposed to the same allergen is well recognised in the context of henna tattoos, with certain genotypes being more susceptible to contact allergy to PPD [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potency of PPD as an allergen is directly related to its concentration and the duration of exposure to the skin; as vendors of black henna are entirely unregulated, the concentration of PPD can reach up to 16%, far in excess of that permissible in hair dyes [2,7,8]. Discordance between siblings who are both exposed to the same allergen is well recognised in the context of henna tattoos, with certain genotypes being more susceptible to contact allergy to PPD [9].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps public health strategy should focus on educating travellers of the potential risks of temporary tattoos, particularly in the population who have had a previous adverse reaction to henna or hair dye. Nonetheless, the application of unadulterated red-brown henna is likely to be safe, except in those individuals with glucose-6-phospate dehydrogenase deficiency [3,8].…”
Section: Discussionmentioning
confidence: 99%
“…Patch tests did not reveal sensitization to PPD or other para-compounds. 2 According to the morphology, which was sharply confined to the site of application, the absence of any eczematous changes, the necrotic epidermis and its evolution, and finally the twice negative patch tests, we concluded that the patient suffered from an acute toxic reaction resulting in a superficial epidermal necrosis with consecutive hypopigmentation. The composition of the tattoo dye was unknown; apparently, it contained an irritant ingredient.…”
Section: Discussionmentioning
confidence: 99%
“…1 Undeclared concentrations between 1% to 63% PPD have been demonstrated in dyes used for henna tattoos. 1,2 This may result in active sensitization in young individuals with long-term sequelae and consequences. 3 We present an unusual irritant reaction from a black henna tattoo without sensitization to PPD but residual hypopigmentation.…”
mentioning
confidence: 99%
“…The content of PPD in temporary henna tattoos has been reported to vary between 0.43 and 15.7 %, which is higher than the allowed concentration of PPD in permanent hair dyes [19,20]. Some preparations of temporary henna tattooing have been observed not to contain brown henna at all [18].…”
Section: Temporary Henna Tattoos (Black Henna)mentioning
confidence: 99%